The Musical Aesthetics of "Likad" Composed by Dewa Ketut Alit - I Gede Ngurah Divo Sentana Divo (Journal of Aesthetics, Creativity and Art Management, 2023)
The music “Likad” was composed in 2020 by Dewa Ketut Alit, a composer born and living in Pengosekan Ubud, Bali. The purpose of this study is to explore (1) the process of formation, the form of the work which consists of, (2) the form, (3) the content or things discussed in this work, and (4) the aesthetics of the form "Likad". The reason for carrying out this research is considering that the work "Likad" contains innovations that are important to examine for clarity, as one manifestation of the development of gamelan music, especially Balinese gamelan. This research is qualitative in nature which reveals the clarity of the creative process, the form of "Likad". The data source for this study is the work of "Likad" himself. The values contained in the work of "Likad" were examined by theory of musical form and theory of aesthetics. Data in this study were obtained through observation, and interviews. The results of this study, among others, the title "Likad" which means ‘difficult’ is reflected in the kotekan pattern of this work which is made more complex than the Balinese traditional pattern. Most of these works present interlocking patterns and a kind of ostinato or short rhythm with repetitions that tend to be more intense. This work raises the issue of Covid-19, in which many parties are ‘likad’ or unable to do activities freely.